The Role of Macrophages in the Development of Human Renal Allograft Fibrosis in the First Year After Transplantation. Issue 9 (6th August 2014) - Toki, D.; Zhang, W.; Hor, K. L. M.; Liuwantara, D.; Alexander, S. I.; Yi, Z.; Sharma, R.; Chapman, J. R.; Nankivell, B. J.; Murphy, B.; O'Connell, P. J.
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the role of infiltrating macrophages in renal allograft fibrosis. Forty‐six protocol renal allograft biopsies obtained 1 year after transplantation were stained with Sirius red to quantify fibrosis and double stained with CD68 and CD206 to identify the proportion of alternatively activated (M2) macrophages. Biopsies were analyzed for gene expression by microarray, which was correlated with macrophage infiltration and the severity of fibrosis. The number of infiltrating CD68+ cells strongly correlated with the percentage of interstitial fibrosis (r = 0.73, p < 0.0001). Macrophage infiltration at 1 year correlated with renal dysfunction at 1, 12 and 36 months posttransplant (estimated GFR low vs. high: 1 month 78 ± 26 vs. 54 ± 19 mL/min, p < 0.01; 12 months 87 ± 29 vs. 64 ± 19 mL/min, p < 0.05; 36 months 88 ± 33 vs. 60 ± 24 mL/min, p < 0.05). Ninety‐two percent of infiltrating macrophages exhibited an M2 phenotype with CD68+ CD206+ dual staining. Gene microarrays demonstrated an alloimmune response with up‐regulation of interferon‐γ‐response genes despite the lack of rejection or inflammatory infiltrate. Consistent with this was the presence of CXCL10 in proximal tubular cells at 3 months. This suggests that M2 macrophage proliferation, or infiltration, was associated with subclinical alloimmune inflammation, tubular injury and progression of fibrosis.